Control of undeclared flavoring of cocoa powders by the determination of vanillin and ethyl vanillin by HPLC. (September 2016) - Pérez-Esteve, Édgar; Lerma-García, María Jesús; Fuentes, Ana; Palomares, César; Barat, José M.
Abstract: A simple protocol for the extraction of vanillin and ethyl vanillin in cocoa powders, followed by analyte quantification using HPLC, has been proposed in this work. After optimizing both, extraction and separation conditions, both analytes were determined in less than 4 min, with relative standard deviation values lower than 2.05% in all cases. Detection limits within 0.04 and 0.06 mg L −1 were achieved. The applicability of the proposed method was evaluated by performing a recovery study, in which a cocoa sample was fortified with both flavors at different concentration levels. In all cases, the recovery values obtained were comprised between 97.5 and 103.1%. The developed method was also successfully applied to analyze 66 commercially available cocoa powders from different brands and markets finding that the 11% of powders contained vanillin and/or ethyl vanillin in concentration ranges comprised between 5.6 and 90.8, and 5.1 and 12.2 mg/100 g for vanillin and ethyl vanillin, respectively. Finally, during the sensory evaluation of cocoa powders, it was revealed that samples containing vanillin show a very round aromatic profile that is very appreciated by the consumers. Thus, the developed method could be useful to control undeclared flavoring and to guarantee food quality and for protecting good manufacturers. Highlights: An HPLC method to detect vanillin/ethyl vanillin in cocoa powders has been developed. Cocoa powders from different brands and markets were analyzed. Vanillin and/or ethyl vanillin contents were detected in 11% of the samples. This method is a tool to guarantee food safety and protect good manufacturers.